2013
DOI: 10.1111/1365-2435.12149
|View full text |Cite
|
Sign up to set email alerts
|

How to avoid errors when quantifying thermal environments

Abstract: Summary 1.Modelling thermal environments at high resolution becomes simpler when using operative temperature, which condenses microclimate and morphology into an index of thermal stress. Operative temperature can be mapped using large numbers of 'operative temperature thermometers', hollow models that duplicate external properties of the animal. 2. As climatologists predict that air will warm by 2-4°C by 2100, biologists must be able to distinguish climate change from systematic errors in operative temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 94 publications
(253 reference statements)
0
109
0
Order By: Relevance
“…Evaporation provides a physiological cooling mechanism (13): Wet-skin T e,max , even in the full sun, allows almost as much reduction in T e,max as shade-use (Fig. 4), compensating almost entirely for radiative heat gain as long as hydration is possible (18).…”
Section: Resultsmentioning
confidence: 99%
“…Evaporation provides a physiological cooling mechanism (13): Wet-skin T e,max , even in the full sun, allows almost as much reduction in T e,max as shade-use (Fig. 4), compensating almost entirely for radiative heat gain as long as hydration is possible (18).…”
Section: Resultsmentioning
confidence: 99%
“…The environmental temperature (heat load or thermal challenge) experienced by a Southern Fiscal on a perch is also an integration of all of these factors, but additionally includes rates of heat transfer via evaporative water loss and input from metabolic heat production (Bakken et al 1985). Furthermore, the shape and posture of a living bird and the properties of its plumage also affect the environmental temperature it experiences in any given location (Bakken et al 1985;Bakken and Angilletta 2014). Bakken et al (1985) found that the correlation between environmental temperatures recorded by taxidermic mounts of Red-winged Blackbirds Agelaius phoeniceus and a matched-size blackbulb thermometer had an r 2 value of 0.968.…”
Section: Discussionmentioning
confidence: 99%
“…colour, shape and size; [46]). We embedded iBUTTON data loggers (DS1921K Maxim) into copper models shaped using a mould of A. cybotes-this new generation of copper models permits automated temperature recording (for details of their construction, see [47]). Methods for calibrating the copper models are given in the electronic supplementary material.…”
Section: (D) Cold-acclimatization Trialsmentioning
confidence: 99%